Replacing punishment: the ethics of alternatives to legal punishment - Gallagher, Scott (Department of Philosophy, 2015)
The purpose of this dissertation is to analyze the morality of putative alternatives to punishment. I will explore what makes them non-punitive, define them, and analyze whether they can be justified. The structure of the dissertation is as follows. The first chapter investigates the concept of punishment. I will defend a definition of punishment: authorized, retributive, intended harm. Then I will proceed to explain the need to justify punishment, and give an overview of how it is at least plausible to believe that no justification has yet succeeded. I will end the chapter with a brief discussion of the requirements of a criminal justice system. The second chapter is about money. I will scrutinize whether the theory of 'pure restitution' may completely replace punishment. I will argue that it cannot, and furthermore I will caution against the widespread use of mandatory monetary restitution. I will also provide a positive argument for the state's duty to provide compensation to victims of violent crime. The third chapter brings in the true heavyweights for non-punitive interventions: offender rehabilitation and offender incapacitation. After defining them, explaining why they are non-punitive, and defending justifications for them, I will conclude that they provide the most substantive opportunities for the state to shift its criminal justice burden s away from punishment. In the fourth chapter I will explore rituals: restorative justice conferences, trial and therapeutic jurisprudence, re-entry ceremonies and apologies. My argument for a minimally punitive regime will come together in the last chapter. In doing so I will explain why a state must rely on punishment to a small but crucial extent, and that punishment can be minimized drastically in comparison to today's practices. I will also address concerns regarding security and deterrence.